Supporting healthcare workers in times of COVID-19 with eye movement desensitization and reprocessing online: A pilot study - Faretta, Elisa; Garau, M. Ignazia; Gallina, Eugenio; Pagani, Marco; Fernandez, Isabel (Frontiers in Psychology, 2022)
The results of a pilot study regarding the adaptation of the group EMDR protocol for the treatment online, for the management of trauma associated with the COVID-19 Pandemic in Italy. The target group were health care workers in a nursing home (Residenza sanitaria assistita, RSA) who decided to live and stay on site during the most acute phase of the Pandemic in order to protect the residents of the home. Scores for perceived PTSD symptoms and quality of emotional experience improved significantly following participation in the therapy programme. These preliminary results confirm the innovative potential of the EMDR protocol when used online on early intervention, to prevent the development of later psychological disturbances.